Türkiye Hayvancılık Sektöründe e-Ticaret Engelleri / E-Commerce Barriers in Turkish Livestock Sector - Aksu, Murat; Gürbüz, Ahmet (Journal of History Culture and Art Research, 2018)
Abstract Electronic commerce (e-commerce); computer, or a device that may be able to perform the same function, and products produced with the help of internet networks, advertising, sales, payment and after-sales service activities. However, the rate of use of e-commerce is not at expected levels for almost every sector and company. Livestock; the economic value of animals, the use of various forms of marketing and marketing. According to TUIK data, the number of bovine animals is approximately 16 million, the number of small ruminants is 45 million, and the number of poultry is 350 million for 2017 year. When you look at the size of the figures, it is a problem that the livestock sector does not spread even though it forms a market large enough for e-commerce. The study was conducted to investigate the reasons for not using the e-commerce system of farmers engaged in animal husbandry in Tokat province and e-commerce hurdles were measured with 20 variables. The research was carried out on 310 animal owners in Tokat province, who voluntarily participated in the face-to-face survey. In the study, factor analysis was conducted to determine the groups of e-commerce hurdles. Whether e-commerce barriers differ according to demographic variables such as education level and number of animals is examined and results and suggestions are presented in the direction of the findings obtained. Öz Elektronik ticaret (e-ticaret); bilgisayar veya aynı işlevi görebilecek bir aygıt ve internet ağları yardımıyla üretilen ürünlerin tanıtılması ve reklamının yapılması, satılması, ödeme ve satış sonrası hizmet faaliyetleri olarak tanımlanabilir. Ancak hemen hemen her sektör ve işletme için avantaj oluşturacağı düşünülen e-ticaretin kullanım oranı beklenen seviyelerde değildir. Hayvancılık; ekonomik değeri olan hayvanların yetiştirilmesi, çeşitli şekillerde yararlanılması ve pazarlanması durumudur. TÜİK verilerine bakıldığında 2017 yılı için büyükbaş hayvan sayısı yaklaşık 16 milyon civarı, küçükbaş hayvan sayısı 45 milyon civarı, kümes hayvanı sayısı ise 350 milyon civarıdır. Rakamların büyüklüğüne bakıldığında hayvancılık sektörünün e-ticaret için yeterli büyüklükte bir pazar oluşturmasına rağmen yaygınlaşmaması bir sorunsaldır. Çalışmada Tokat ilinde hayvancılıkla uğraşan çiftçilerin e-ticaret sistemini kullanmama sebepleri araştırılmış ve e-ticaret engelleri 20 değişken ile ölçülmüştür. Araştırma, yüz yüze anket yöntemiyle katılımı gönüllü olarak kabul eden, Tokat ilinde bulunan 310 hayvan sahibine yapılmıştır. Çalışmada e-ticaret engellerinin guruplarını saptamak için faktör analizi yapılmıştır. E-ticaret engellerinin eğitim durumu ve hayvan sayısı gibi demografik değişkenlere göre farklılaşıp farklılaşmadığına bakılmış ve elde edilen bulgular doğrultusunda sonuç ve öneriler sunulmuştur.